Organizational commitment in a portuguese public higher education institution - Ribeiro, Maria Isabel (2022)
Individuals with high organizational commitment protect organizational heritage, share organizational goals and remain in the organization in good and bad times (Batugal & Tindowen, 2019). So, this research intended to determine the level of organizational commitment and to determine whether the type of employment contract is a differentiator factor of the organizational commitment. Therefore, a quantitative and cross-sectional study was carried out based on the application of a questionnaire to the employees of a Public Higher Education institution, located in Trás-os-Montes region (Northeast Portugal). The questionnaire included the scales of organizational commitment of the three-dimensional model developed by Meyer and Allen (1991), namely, affective, calculative and normative. The administration of the questionnaire took place from October 22, 2021 to January 4, 2022 having obtained 105 responses. The results showed that the respondents' global commitment to the organization was moderate. Taking into account the three dimensions of the model, employees registered higher levels of affective commitment, moderate levels of calculative commitment and lower levels of normative commitment. Additionally, it was found that the type of employment contract was a differentiator factor of organizational commitment in only two of the three dimensions of the organizational commitment model, namely, normative and calculative. In fact, in the calculative commitment, employees with an uncertain-term contract registered higher levels of organizational commitment. On the contrary, in the normative commitment, employees with a fixed-term contract registered higher levels of organizational commitment.